An exploration of asset returns in a production economy with relative habits - Budría, Santiago (2015)
This paper explores asset returns in a production economy with habit forming households. I show that a model with capital adjustment costs and relative habits is consistent with salient financial facts, such as the equity premium, the market price of risk, and the riskfree interest rate. These predictions are not at odds with good business cycle predictions. In the model economy investment is strongly procyclical and more volatile than output, which in turn is more volatile than consumption. Moreover, consumption growth is positively autocorrelated and negatively (positively) correlated with future (past) stock returns.